Early Childhood Education Reform in Pakistan: Challenges, Innovations, and Future Prospects - Artipah, Artipah; Sain, Zohaib Hassan; Asfahani, Asfahani; Sa'diyah, Sa'diyah (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research investigates the landscape of Early Childhood Education (ECCE) reforms in Pakistan, aiming to explore the sector's challenges, innovations, and prospects. A systematic literature review identified key challenges such as limited access to quality education and a shortage of trained educators, encouraging the exploration of innovative solutions, including technology integration and community-based centers. The analysis shows promising prospects for ECD reform in Pakistan, contingent on continued government investment, strengthened partnerships, and targeted interventions. These findings suggest promising prospects for ECD reform in Pakistan, contingent on continued government investment and strategic partnerships. So, this research contributes to the ongoing discourse regarding improving the quality and accessibility of early childhood education in Pakistan.